2019
DOI: 10.1101/577478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced proteasome activity in the aging brain results in ribosome stoichiometry loss and aggregation

Abstract: A progressive loss of protein homeostasis is characteristic of aging and a driver of neurodegeneration. To investigate this process quantitatively, we characterized proteome dynamics during brain aging by using the short-lived vertebrate Nothobranchius furzeri and combining transcriptomics, proteomics and thermal proteome profiling. We found that the 25 correlation between protein and mRNA levels is progressively reduced during aging, and that post-transcriptional mechanisms are responsible for over 40% of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
67
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 72 publications
13
67
1
Order By: Relevance
“…Promisingly, the investigators found an increase in both total protein aggregation and specific aggregation [Keywords: aneuploidy; protein aggregation; protein homeostasis] of proteins encoded by the duplicated chromosome in almost all 16 strains. The overwhelming majority of proteins that aggregated in all strains were components of ribosomes, an observation consistent with several recent reports linking the aggregation of ribosomal proteins with proteotoxic stresses (Pathak et al 2017;Sacramento et al 2019;Tye et al 2019).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Promisingly, the investigators found an increase in both total protein aggregation and specific aggregation [Keywords: aneuploidy; protein aggregation; protein homeostasis] of proteins encoded by the duplicated chromosome in almost all 16 strains. The overwhelming majority of proteins that aggregated in all strains were components of ribosomes, an observation consistent with several recent reports linking the aggregation of ribosomal proteins with proteotoxic stresses (Pathak et al 2017;Sacramento et al 2019;Tye et al 2019).…”
supporting
confidence: 90%
“…This study also brings to the fore another phenomenon observed during cancer but also during aging: the loss of protein complex stoichiometry (Janssens et al 2015). Ribosomes (the major components aggregating in the present study) are especially sensitive to this, as shown by a recent study in turquoise killifish, where ribosomal subunits were enriched in aggregates from aged brains (Sacramento et al 2019). Recent advances in global protein complex profiling techniques (e.g., size exclusion chromatography [SEC]-sequential window acquisition of all theoretical mass spectra [SWATH]-MS) (Heusel et al 2019) will undoubtedly prove fruitful for characterizing protein stoichiometry changes under such conditions.…”
mentioning
confidence: 51%
“…Nevertheless, our results suggest an essential partnership between TDP-43 and HSP70 chaperones in driving and maintaining TDP-43 phase separation. Future efforts are now needed to determine the identities of the TDP-43 acetylases and deacetylases and whether there are age-dependent changes in their activities that may synergize with the known age-dependent decline in proteasome activity (63,64) to mediate stress-induced TDP-43 phase separation in age-related neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The iPSCs were differentiated according to a modified version of Martinez et al (62), based on the established strategy of dual-SMAD inhibition (63,64). iPSC dishes at 60-80% confluency Primary antibodies were diluted in the blocking buffer, and cells were incubated with primary antibody over night at 4ºC.…”
Section: Plasmidsmentioning
confidence: 99%
“…Intriguingly, recent studies have also indicated that ribosomes are especially susceptible to the protein aggregates that are formed either due to abnormal protein stoichiometry during aneuploidy or due to protein aggregation in aged brains 40,41 . Our recent and earlier 13 studies suggest that the ribosome when placed in the vicinity of protein aggregate formation have a tendency to co-aggregate, thereby providing a plausible explanation to the predominance of ribosomal proteins in the aggregates observed in these studies 40,41 . The inhibition of tau-ribosome electrostatic interactions in the presence of added polyanions, like heparin and tRNA, indeed could inhibit K18 induced tau aggregation.…”
Section: Scientific Reports |mentioning
confidence: 99%